Perancangan Sequence Penambangan Bulan Januari dan Februari Tahun 2025 pada PT Putra Perkasa Abadi Site SKS - Eka Taufiqur Rahman; Deddy Nan Setya Putra Tanggara; Ferdinandus Ferdinandus; Noveriady Noveriady; I Putu Putrawiyanta (Pusat riset dan Inovasi Nasional, 2026)
Mining sequence design is one of the important stages in open pit mining activities that aims to organize the excavation stages so that production activities run effectively, efficiently, and in accordance with the established targets. This research was conducted at PT Putra Perkasa Abadi Site SKS with the aim of designing a mining sequence in January and February 2025. The methods used include analysis of topographic data, geology, pit design, and monthly production targets. The data was processed using mining software to determine the excavation sequence based on elevation, overburden volume, and coal reserves. The design results show that the total planned overburden and coal volume is able to meet the company's production targets by considering slope stability and the efficiency of digging and loading equipment. In addition, the resulting sequence design also takes into account aspects of work safety and field operational conditions, such as mine road access and drainage systems. With a structured design, it is expected that mining activities during this period can run according to schedule, minimize operational obstacles, and support the achievement of production targets and cost efficiency at PT Putra Perkasa Abadi Site SKS.